Snapping Biceps Femoris Repair: A Rare Cause of Lateral Knee Pain - Adam J. Tagliero MD; Vaibhav R. Tadepalli MD; Brian C. Werner MD (SAGE Publishing, 2024)
Background: Snapping biceps femoris syndrome (SFS) represents a rare clinical entity in which the biceps femoris subluxates over the fibular head in deep flexion. Two primary pathophysiologies have been described including a prominent or abnormal fibular head morphology. Others have implicated an anomalous biceps femoris insertion. The diagnosis is made clinically, with operative and nonoperative intervention strategies available for treatment. Indications: SFS often results in audible snapping and associated pain at the lateral fibular head. When recalcitrant to nonoperative management, surgical intervention can lead to resolution of symptoms. We present the case of a college-aged male who has bilateral symptoms, worse on the right, which have resulted in significant activity modification and daily discomfort recalcitrant to anti-inflammatory medication and physical therapy. Technique Description: The patient was placed supine on the operating room table with an ipsilateral bump under the hip to assist in exposure of the lateral aspect of the knee. Examination under anesthesia (EUA) confirmed the snapping biceps femoris. A lateral approach to the knee and a common peroneal neurolysis was performed. The biceps femoris insertional anatomy was examined for anomalous tendon insertion or insertional tearing. The prominent fibular head was exposed and resected, with careful attention not to disrupt the lateral collateral ligament or popliteofibular ligament insertion sites. The biceps femoris was then repaired to the prepared bony bed of the fibula with one double-loaded suture anchor. Repeat EUA confirmed complete resolution of snapping even with maximal internal rotation of the tibia; this was carefully examined again with the tourniquet deflated to ensure its compressive effect was not partially responsible for the resolution. Results: Published data pertaining to SFS is limited to case reports and small case series. With appropriate indications, surgical intervention yields promising results with a high percentage of patients returning to prior level of activity or prior participation level in sport. Discussion/Conclusion: SFS can be diagnosed with a careful clinical assessment. When recalcitrant to nonoperative management, it is effectively treated with surgical intervention to restore normal fibular anatomy, and prevent recurrent instability and persistent pain. The presented technique allows for appropriate management of these rare injuries. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.